Molecular imaging with optical coherence tomography using ligand-conjugated microparticles that detect activated endothelial cells: rational design through target quantification. - Jefferson, A; Wijesurendra, R; McAteer, M; Digby, J; Douglas, G; Bannister, T; Perez-Balderas, F; Bagi, Z; Lindsay, A; Choudhury, R (2011)
OBJECTIVES: Optical coherence tomography (OCT) is a high resolution imaging technique used to assess superficial atherosclerotic plaque morphology. Utility of OCT may be enhanced by contrast agents targeting molecular mediators of inflammation. METHODS AND RESULTS: Microparticles of iron oxide (MPIO; 1 and 4.5 μm diameter) in suspension were visualized and accurately quantified using a clinical optical coherence tomography system. Bound to PECAM-1 on a plane of cultured endothelial cells under static conditions, 1 μm MPIO were also readily detected by OCT. To design a molecular contrast probe that would bind activated endothelium under conditions of shear stress, we quantified the expression (basal vs. TNF-activated; molecules μm(-2)) of VCAM-1 (not detected vs. 16 ± 1); PECAM-1 (132 ± 6 vs. 198 ± 10) and E-selectin (not detected vs. 46 ± 0.6) using quantitative flow cytometry. We then compared the retention of antibody-conjugated MPIO targeting each of these molecules plus a combined VCAM-1 and E-selectin (E+V) probe across a range of physiologically relevant shear stresses. E+V MPIO were consistently retained with highest efficiency (P < 0.001) and at a density that provided conspicuous contrast effects on OCT pullback. CONCLUSION: Microparticles of iron oxide were detectable using a clinical OCT system. Assessment of binding under flow conditions recommended an approach that targeted both E-selectin and VCAM-1. Bound to HUVEC under conditions of flow, targeted 1 μm E+V MPIO were readily identified on OCT pullback. Molecular imaging with OCT may be feasible in vivo using antibody targeted MPIO.